2011
DOI: 10.1016/j.ecosys.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nominal exchange rate volatility on real macroeconomic performance in the CEE countries

Abstract: Décembre 2009 GATE Groupe d'Analyse et de Théorie Économique UMR 5824 du CNRS 93 chemin des Mouilles -69130 Écully -France B.P. 167 -69131 Écully Cedex Tél. +33 (0)4 72 86 60 60 -Fax +33 (0)4 72 86 60 90 Messagerie électronique gate@gate.cnrs.fr Serveur Web : www.gate.cnrs.fr Abstract This paper analyzes the relation between nominal exchange rate volatility and several macroeconomic variables, namely real per output growth, excess credit, foreign direct investment (FDI) and the current account balance, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 58 publications
1
6
0
1
Order By: Relevance
“…The results unambiguously suggest that countries in a monetary union have a greater volume of trade and less volatility in the real exchange rate than countries using their own domestic currency. Arratibel, Furceri, Martin, and Zdzienicka (2011) analysed both the EU and the CEE countries. Using panel estimations for the period between 1995 and 2008, they found that lower exchange rate volatility is associated with greater economic growth and a larger current account deficit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results unambiguously suggest that countries in a monetary union have a greater volume of trade and less volatility in the real exchange rate than countries using their own domestic currency. Arratibel, Furceri, Martin, and Zdzienicka (2011) analysed both the EU and the CEE countries. Using panel estimations for the period between 1995 and 2008, they found that lower exchange rate volatility is associated with greater economic growth and a larger current account deficit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While (Arratibel and Zdzienicka, 2011) documented that there is the existence of the negative and significant relationship of the volatility of exchange rates on FDI in member countries of the EU to Central and Eastern Europe. As (Cushman, 1988) documented that there is a positive association between exchange rate uncertainty and FDI in the United States.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The price of a country's currency, seen as a commodity, is essentially determined by the relationship between supply and demand in the forex market. The fluctuations of the exchange rate exercise great influence on macroeconomic operation [1] and the implementation of monetary policy [2,3]. From the micro perspective, both enterprises and individuals are more likely to succumb to the risks under a floating exchange rate regime than under a fixed regime since production and consumption behaviors tend to change accordingly when dealing with uncertainty [4].…”
Section: Literature Reviewmentioning
confidence: 99%